Evaluation of the Short- and Long-Term Effectiveness of Pulsed Radiofrequency and Conventional Radiofrequency Performed for Medial Branch Block in Patients with Lumbar Facet Joint Pain - Abdurrahman Çetin; Abdulkadir Yektaş (Pain Research and Management)
Background. Diagnosis of lumbar facet joint disease is the sum of the combinations consisting of history, physical activity, and diagnostic imaging frequently including computed tomography and magnetic resonance imaging scans. Prevalence of facet-based chronic low back pain is 15–45%. Intra-articular injections with corticosteroid or medial branch block are traditionally used prevalently in the management of chronic low back pain due to lumbar facet joints. However, the evidence levels of these procedures are at either a low or a medium level. Radiofrequency neurolysis of the lumbar medial branch can be used as an alternative in the management of lumbar facet joint pain. There are two types of radiofrequency applications for radiofrequency neurolysis as pulsed radiofrequency and conventional radiofrequency. Materials and Methods. Patients with lumbar facet pain were separated into 2 groups. Group 1 (n=75): patients were given pulsed radiofrequency under fluoroscopy. Group 2 (n=43): patients were given conventional radiofrequency under fluoroscopy. Pre-op and post-op 1st, 3rd, and 6th month and 1st and 2nd year Visual Analogue Scale values of all patients were asked, recorded, and statistically compared. Visual Analogue Scale values of the groups in the same months were compared as well. At the end of the second year, Odom criteria of both groups were recorded and statistically compared. Results. Preoperation Visual Analogue Scale values and postoperation 1st, 3rd, and 6th month and 1st and 2nd year Visual Analogue Scale values were compared in Group 1 and Group 2, and there was a statistically significant difference between preoperation Visual Analogue Scale values and postoperation 1st, 3rd, and 6th month and 1st and 2nd year Visual Analogue Scale values in both groups. However, the number of repetitions of the operation was higher in Group 1. In the comparison of Odom criteria for both groups at the end of the second year, it was observed that the patients in Group 2 were more satisfied with the treatment. Conclusion. Conventional radiofrequency in patients with lumbar facet joint pain for medial branch neurolysis effectively decreases Visual Analogue Scale values in both short and long term. The quality of life and daily activities of patients were better at conventional radiofrequency.